Turning Vietnamese. (Economist, 1994)
In Vietnam, where approximately 90 percent of the operating software on PCs is pirated, a forthcoming copyright law that includes computer programming has one fatal loophole. Software and other original material invented in Vietnam will automatically be protected, but foreign material will only qualify if it is available for sale in Vietnam within 30 days of its first publication. The director of the National Office for Copyright Protection, Thuong Thuan, agrees that foreign material is badly protected, but he argues that it will be taken care of when Vietnam joins the Bern Convention for the Protection of Literary and Artistic Work. The problem is that Vietnam will not be allowed to join the convention as long as it keeps the 30-day requirement. The reasons for Vietnam's uncooperative behavior are outlined.